Chinese and Western sports philosophy and their differences - Yuanjiao Zhu; Rui Du (Trans/Form/Ação)
Chinese and Western sports are in two different social systems. Because of the difference in their origin, cognition and value trend, two kinds of sports cultures of different natures have been created. Each of which interprets the characteristics of human civilization in different forms. In Chinese culture, sports are often closely associated with Taoist and Confucian philosophies. Taoism emphasizes “letting nature take its course”, and physical exercise is regarded as a means of harmonizing body and mind, and achieving unity of body and mind. Confucianism believes that sports are to cultivate people’s morality and etiquette, not just to pursue physical limits. In contrast, Western sports philosophy usually emphasizes competition, challenge and self-transcendence. This idea can be traced back to ancient Greece’s Olympic spirit, which is to demonstrate individual honor, strength and courage through physical exercise. In general, although Chinese and Western sports philosophies both believe that sports are an exercise for the human body and spirit, they differ in values, goals and methods. This study takes the comparison between traditional Chinese sports culture and Western sports culture as the starting point and attempts to analyze the commonalities and differences between the two. This has important practical significance for enriching world sports culture and promoting the development of world sports culture.